The study of relationship between the truncal obesity (WHR) and type-II diabetes (NIDDM) in women aged 30 to 60 years, Tabriz - P.Pourabdollahi (M.Sc); N.Rabeti (B.Sc); H.Kooshavar (M.Sc) (مجله دانشگاه علوم پزشکی گرگان, 2002)
It is generally recognized diabetes in more prevalent in women than men, besides that there is a close relationship between diabet, type of obesity and body fat distribution. In a descriptive-analytical study, 100 diabetic women aged 30-60 years old referring to diabetic clinic compared with 100 healthy subjects who were similar to the sample group with respect to age and sex. The results showed that BMI of majority women on both groups were in the range of 24.9-29.9, on the other hand 33% of women in control group and 26% patients suffered from the grade one obesity. Minimum ratio of waist-to-hip ratio (WHR) in patients was 0.72 and in healthy women was 0.47. In control group 90% and in healthy subjects 74% of women suffered from upper-truncal obesity (WHR>0.8). A significant difference was found (P=0.04) between the WHR ratio in women control and healthy group. To prevent the fat distribution in the area of stomach and upper truncal, increasing activity and dietary control are suggested.